At the Intersection of Biomaterials and Gene Therapy: Progress in Non-viral Delivery of Nucleic Acids - Uludag, Hasan; Ubeda, Anyeld; Ansari, Aysha (Frontiers in Bioengineering and Biotechnology, 2019)
Biomaterials play critical roles in technologies intended to deliver therapeutic agents in clinical settings. Recent explosion of our understanding of how cells utilize nucleic acids has garnered excitement to develop a range of older (e.g., antisense oligonucleotides, plasmid DNA and transposons) and emerging (e.g., short interfering RNA, messenger RNA and non-coding RNAs) nucleic acids agents for therapy of a wide range of diseases. This review will summarize biomaterials-centered advances to undertake effective utilization of nucleic acids for therapeutic purposes. We first review various types of nucleic acids and their unique abilities to deliver a range of clinical outcomes. Using recently emerging T-cell based therapy as a case in point, we summarize various possibilities for utilizing biomaterials to make an impact in this exciting therapeutic intervention technology, with the belief that this modality will serve as a therapeutic paradigm for other types of cellular therapies in the near future. We subsequently focus on contributions of biomaterials in emerging nucleic acid technologies, specifically focusing on the design of intelligent nanoparticles, deployment of mRNA as an alternative to plasmid DNA, long-acting (integrating) expression systems, and in vitro/in vivo expansion of engineered T-cells. We articulate the role of biomaterials in these emerging nucleic acid technologies in order to enhance the clinical impact of nucleic acids in the near future.